Clinical spectrum of lysosomal storage disorders in children - Kariyappa, Pushpalatha; Manjunath, Dakshayani; Sarode, Sushmitha; Rao, Udayakumar SSeetharam (International Journal of Contemporary Pediatrics, 2022)
Lysosomal storage diseases (LSDs) are inherited metabolic diseases that are characterized by the accumulation of various toxic metabolites as a result of enzyme deficiencies. LSDs comprises of more than 50 diseases and are classified on a biochemical basis and the type of accumulated substrate. Most of the LSDs are inherited as autosomal recessive disorders with a few exceptions. Gaucher disease is the most common LSD. Clinical presentation of these children usually includes- anaemia, easy bruising, abnormally enlarged liver and/or spleen. We report a case series of 12 children with LSD. Among them 9 (75%) with GD, 3 (25%) with MPS. Based on the symptoms, in reducing order of frequency, children presented with generalised weakness, growth failure, abdominal distension, and developmental delay. 3 children with MPS had coarse facial features with reduced joint movements and hearing impairment. On examination, 5 children (41.6%) weighed less than third percentile, 9 (75%) had short stature, 10 (83%) had moderate to severe visceromegaly, CNS involvement in 2 children seen as hypotonia, occulomotor apraxia. Hematological parameters in all revealed- anaemia/leucopenia/thrombocytopenia- with two or more of the cell lines being affected. Bone marrow biopsy done in 9 (75%) children all of which were abnormal. Most of the children had enzyme activity levels between 0 to less than 15% of the normal reference range of the respective enzyme. ERT was initiated in 9 children (7 GD children and 2 MPS child) and followed up, showed a gradual amelioration in the symptoms by 1 year of regular ERT.